Electroconvulsive therapy for depression in Parkinson's disease: systematic review of evidence and recommendations. (April 2016) - Borisovskaya, Anna; Bryson, William Culbertson; Buchholz, Jonathan; Samii, Ali; Borson, Soo
Aim: We performed a systematic review of evidence regarding treatment of depression in Parkinson's disease (PD) utilizing electroconvulsive therapy.Methods: The search led to the inclusion of 43 articles, mainly case reports or case series, with the largest number of patients totaling 19.Results: The analysis included 116 patients with depression and PD; depression improved in 93.1%. Where motor symptoms' severity was reported, 83% of patients improved. Cognition did not worsen in the majority (94%). Many patients experienced delirium or transient confusion, sometimes necessitating discontinuation of electroconvulsive therapy (ECT). Little is known about maintenance ECT in this population.Conclusion: ECT can benefit patients suffering from PD and depression. We recommend an algorithm for treatment of depression in PD, utilizing ECT sooner rather than later.